ENCAPSULATION: AN ALTERNATIVE FOR APPLICATION OF PROBIOTIC MICROORGANISMS IN THERMALLY PROCESSED FOODS - Cavalheiro, Carlos Pasqualin (2015)
The consumption of probiotics has increased considerably in recent years and many probiotic foods are already available on the market. Among probiotic microorganisms, Lactobacillus and Bifidobacterium are the most common. However, the application of this kind of microorganism is still limited to foods that not pass through extreme onditions of temperature during processing. Thus, encapsulation techniques are emerging as an alternative to use probiotic microorganisms in thermally processed foods. The main encapsulation techniques are extrusion, spraydrying and emulsification, which each one has its advantages and disadvantages. Currently, various materials can be used for encapsulating bacteria; however, alginate is the most commonly used. To obtain probiotic capsules with high viability even after heat treatments is necessary to associate heat tolerant probiotic strains and appropriated materials and encapsulation techniques.